1994
DOI: 10.1021/j100078a022
|View full text |Cite
|
Sign up to set email alerts
|

Wettability, Surface Morphology, and Stability of Long-Chain Ester Multilayers Obtained by Different Langmuir-Blodgett Deposition Types

Abstract: Methyl arachidate Langmuir-Blodgett multilayers, built up by X-, XY-and Y-type transfers, are characterized by means of contact angle measurements, and optical and atomic force microscopy under ambient conditions. Contact angle investigation shows identically high hydrophobicity of the surfaces produced by X-and Y-type depositions, implying molecular overturning during the X-type transfer. This overturning has not been detected in the previous X-ray study of small numbers of deposited fatty acid methyl ester m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…22 Therefore, molecules deposited so as to form X films must rearrange during or shortly after deposition, so that the Y-structure is produced. 23 In the case of ACC it appears that the Y-type layered structure forms from the Z-type deposition procedure.…”
Section: Resultsmentioning
confidence: 99%
“…22 Therefore, molecules deposited so as to form X films must rearrange during or shortly after deposition, so that the Y-structure is produced. 23 In the case of ACC it appears that the Y-type layered structure forms from the Z-type deposition procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 14 provides a schematic definition of what is meant here by the term "overturn". Evidence of molecular overturn was obtained by Angelova et al (1994), who prepared Langmuir-Blodgett multilayers from long-chain fatty esters. Surprisingly, contact angle experiments yielded essentially the same results irrespective of whether the outermost molecular layer was inward-facing or out-ward facing.…”
Section: Instability Of Fatty Acid Monolayers To Molecular Overturnmentioning
confidence: 97%
“…Goddard and Ackill 1963;Binks 1991 Fatty acids within natural samples of wood and related bioresources are invariably mixtures, containing a range of unsaturated (such as oleic, linoleic, and linolenic acids) and saturated (such as stearic acid) components, in addition to triglyceride fats and other hydrophobic compounds such as -sitosterol (pine oil). Studies have shown that when such mixtures are collected as monolayer films, some of the component compounds may become self-segregated into separate domains (Angelova et al 1994;Lieckfeldt et al 1994;Johann et al 2001;Ocko et al 2002; Torrent-Burgués 2018).…”
Section: Self-assembly At Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that these divalent cations dramatically increased the film stability during the deposition. It has been observed that the transfer of Langmuir film from the gas-liquid interface onto a solid substrate is dependent on the characteristics of the sub-phase, solid substrate and deposition speed [12][13][14][15]. Previous studies [16][17][18][19][20][21][22][23] have revealed that divalent ions interact with arachidic acid (AA) and stearic acid (SA) in each layer to form "di-soap," which could enhance film stability.…”
Section: Introductionmentioning
confidence: 99%